PENERAPAN APLIKASI KREDIT POIN PELANGGARAN SISWA BERBASIS SMS GATEWAY : Abuse;Discipline;School;SMS Gateway;Website. - Puad, Lailyn; Limia, Rike; Kusumah Rani, Endah (LP2M Universitas Nurdin Hamzah, 2020)
School is one of the educational institutions that has a function to shape student personalities for the better through various kinds of activities both formal and informal. One of the steps that can be taken is to apply reward and punishment which can motivate students not to violate or do something good. This becomes more attractive and structured by making this system run in an application. The use of a web-based system and using SMS Gateway technology makes this application more interactive and useful for the progress of schools with increasing student discipline.